A COMPETENT APPROACH TO FORMING THE PEDAGOGICAL SKILLS OF THE FUTURE PRIMARY SCHOOL TEACHER - Малишева, Л.С.; Заболотенко, О. (Modern engineering and innovative technologies, 2024)
The article analyzes the structure of pedagogical abilities, reveals the content of the concept of personality abilities and features of professional abilities of teachers. Different classifications of the structure and types of pedagogical abilities of p